Translation is Beyond lexical meaning : study through some select terms - Gayathree, S. (Arima Nokku, 2018)
Generally people think that anyone who knows more than one language can do translation. But it is not so, there are so many factors to be considered to meet the satisfaction of the target read- ership. Every lexical expression has its own significance. A trans- lator must transfer those implied things from the original into the target language. While doing so, a translator can utilize the tools such as dictionary, thesaurus, glossary and encyclopedia. But it is the co-skills of the translator to apply the proper terms with the appropriate meanings in the right places. So, beyond referring a proper tool a translator should have the skill to find the appropri- ate equivalent and to apply them properly to suit the target lan- guage. This study aims at identifying and analyzing such applica- tions through some select terms. With this scope, this study in- tends to refer the proper references as translation is not merely finding the equivalents. Some select terms sources of this study are the lexicons and dictionaries.